Exploring the Impact of Project-Based Learning on University Students’ Essay-Writing Ability - Andi Patmasari; Afrillia Anggreni; Muhammad Ismail (AL-ISHLAH: Jurnal Pendidikan, 2025)
Project-Based Learning (PjBL) offers an instructional approach that emphasizes student autonomy, collaboration, and real-world application, which may enhance essay-writing ability. This study aims to (1) examine the effect of PjBL on university students’ essay-writing ability and (2) evaluate its effectiveness in improving writing performance. A quasi-experimental design with a sequential explanatory mixed-methods approach was employed. The participants were students in Class B of the English Education Study Program at Tadulako University, selected through purposive sampling. Quantitative data were gathered through pre- and post-tests and analyzed using a paired samples t-test and normalized gain (N-gain) scores. Qualitative data from learning logs and interviews were analyzed thematically to explain the quantitative findings. The t-test indicated a statistically significant improvement in students’ writing scores after the PjBL intervention (p = 0.000). However, the N-gain score was 0.1978, placing the effectiveness in the “low” category. Qualitative findings showed that students positively perceived PjBL, noting enhanced critical thinking, creativity, and collaboration. Nevertheless, several challenges emerged, including uneven group participation, cognitive overload, and misalignment between assessment and learning activities. Despite statistical significance, the low effectiveness suggests limitations in task design, assessment alignment, and learner readiness. These factors may have constrained the impact of PjBL on measurable writing outcomes. PjBL significantly affected students’ essay-writing ability, but its practical effectiveness was limited. Given the study’s reliance on a single purposive sample, generalizability is restricted. Future research should include larger, diverse samples and refine instructional design to maximize PjBL’s pedagogical benefits.